Approaching a neoclassical scenario: the labor market in China after the Lewis turning point - Fang Cai (China Finance and Economic Review, 2013)
As China passes through its Lewis turning point characterized first by the appearance of a labor shortage and a constant increase in wages, its labor market shows both features of the dual economy and neoclassical growth. This paper first depicts the trend of population as a root cause of the labor market transition from dual economy to neoclassical scenario. It then reveals the changed labor market profile - the labor shortage and wage increase. By examining three major groups of employment, namely, migrant workers, university graduates, and urban vulnerable workers, it tries to explore those unique characteristics of the labor market in such a transitional period and draws policy implications.
Keywords: 330; Demographic transition; Lewis turning point; Labor market institutions